The influence of social networks, social capital, and the ethnic community on the U.S. destination choices of Mexican migrant men. - Sue, Christina A.; Riosmena, Fernando; LePree, Joshua (Journal of Ethnic & Migration Studies, 2019)
Compared to the overwhelming emphasis on the causes of international migration, less attention has been paid to immigrant destination choice. Studies which have addressed destination outcomes are generally quantitative in nature and have focused on macro-level explanations. In this article, we adopt a qualitative approach to examine undocumented Mexican male migrants' decision-making processes about the destination, demonstrating how the interplay between social networks, social capital, and individual circumstance influences their U.S. destination choices, both when migrating from Mexico and when relocating within the United States. Based on seventy semi-structured, in-depth interviews with primarily undocumented Mexican migrants residing in Colorado, we detail the specific mechanisms that guided them to particular destinations. Our findings illustrate the importance of the geographical diversity of social ties, the type of migration (international vs. internal), the kind and strength of ties, and the form of interpersonal interactions with ties, for respondents' destination outcomes. In addition, our findings challenge the notion that the presence of a co-ethnic community is consistently viewed by migrants as a destination incentive.